MOTIVASI DAN HASIL BELAJAR AL-QUR’AN HADITS MELALUI MODEL PEMBELAJARAN BERBASIS PORTOFOLIO - Siti Umaiyah; Nurul Hidayati Murtafiah; Tamyis (UNISAN JURNAL, 2023)
The purpose of this study was to determine the motivation and learning outcomes of Al-Qur'an Hadith through a portfolio-based learning model at MA Hidayatul Mubtadiin Jati Agung. While this research uses descriptive qualitative research methods. Data collection was carried out using the method of observation (observation), and documentation. Data analysis was performed using triangulation, namely data reduction, data display and verification. Based on the results of data analysis in the discussion of the previous chapter, it can be concluded that they are able to develop motivation and learning outcomes of the Qur'an hadith through a portfolio-based learning model at MA Hidayatul Mubtadiin Jati Agung, namely by active student learning, cooperative student study groups, creative teaching, discovery method and inquiry method.